ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN PENGGUNA LAYANAN E-GOVERNMENT Studi Kasus Pada Modul Penerimaan Negara Generasi 2 - Ariessa Purwidyasari; Muhammad Syafruddin (Diponegoro Journal of Accounting, 2017)
This research aims to identify the factors that determine customer satisfaction of e-government services. Based on theory and relevant previous research, five hypothesis are formulated, which contain five independent variables, security and privacy, trust, accessibility, awareness of public services, and quality of public services, and one dependent variables, customer satisfaction. Data used in this research is primary data collected through questionnaire distributed to 90 treasurer or finance staff as institution taxpayer in Blitar State Treasury Authority’s precinct. Based on multiple linear regression, trust, accessibility, and quality of public services are significantly influence customer satisfaction. These findings may utilized by Ministry/Institutions to unveil the key factors in developing e-government which are compatible with citizens’ needs and desire as the public service customer.